Regulation of O-GlcNAcylation on endothelial nitric oxide synthase by glucose deprivation and identification of its O-GlcNAcylation sites - He, An; Hu, Shupeng; Pi, Qiangzhong; Guo, Yongzheng; Long, Yang; Luo, Suxin; Xia, Yong (Scientific reports, 2020)
As an energy-sensitive post-translational modification, O-GlcNAcylation plays a major role in endothelial nitric oxide synthase (eNOS) activity regulation. However, effects of glucose deprivation on eNOS O-GlcNAcylation and the presence of novel O-GlcNAcylation sites of eNOS under glucose deprivation remain unknown. Hence, we aim to determine the effects of glucose deprivation on O-GlcNAcylation and novel O-GlcNAcylation sites of eNOS. Bovine aortic endothelial cells (BAECs) and Sprague–Dawley rats were induced by glucose deprivation and their eNOS O-GlcNAcylation was subjected to immunoblotting. eNOS and transfected eNOS were purified by pull-down assay and immunoprecipitation respectively. Novel O-GlcNAcylation sites of eNOS were predicted by HPLC–MS and MS/MS Ion and determined by immunoblotting. eNOS activity was detected by Elisa and isotope labeling method. In BAECs and rat thoracic aorta, low glucose-associated activation of eNOS was accompanied by elevated O-GlcNAcylation, which did not affect O - linked serine phosphorylation at 1179/1177 residues. Changes in this post-translational modification were associated with increased O-GlcNAc transferase (OGT) expression and were reversed by AMPK knockdown. Immunoblot analysis of cells expressing His-tagged wild-type human eNOS and human eNOS carrying a mutation at the Ser1177 phosphorylation site confirmed an increase in O-GlcNAcylation by glucose deprivation. A marked increase in O-GlcNAcylation indicated that eNOS contained novel O-GlcNAcylation sites that were activated by glucose deprivation. Immunoblot analysis of cells expressing His-tagged human eNOS carrying a mutation at Ser738 and Ser867 confirmed an increase in O-GlcNAcylation by glucose deprivation. Conversely, in His-tagged human eNOS carrying a mutation at Thr866, O-GlcNAcylation was unaffected by glucose deprivation. Differences in culture conditions were identified using two-way analysis of variance (ANOVA), one-way ANOVA, and unpaired Student’s t -test. Glucose deprivation increases O-GlcNAcylation and activity of eNOS, potentially by the AMPK-OGT pathway, suggesting that Thr866 is a novel O-GlcNAcylation site involved in glucose-deprivation mediated eNOS activation.